Effect of phenylephrine infusion on hypotension induced by the beach chair position: A prospective randomized trial. Issue 28 (10th July 2020) - Ko, Myoung Jin; Kim, Hyojoong; Lee, Hyun-seong; Lee, Soo Jee; Park, Yei Heum; Bang, Jin-Young; Lee, Ki Hwa
Abstract: Background: The beach chair position (BCP), used during shoulder surgery, is associated with hypotension, bradycardia, and risk of cerebral hypoperfusion. Phenylephrine is commonly used as a first treatment of choice of intraoperative hypotension during surgery. We evaluated the hemodynamic effects of 2 doses of intravenous phenylephrine infusion administered before being placed in BCP for arthroscopic shoulder surgery. The primary endpoint was the incidence of hypotension after positional change. Methods: Sixty-six patients were randomized to receive either intravenous normal saline (group NS) or intravenous phenylephrine infusion (0.5 μg/kg/min, group LP or 1.0 μg/kg/min, group HP) for 5 minutes before being placed in the BCP. Mean arterial pressure(MAP), heart rate, stroke volume variation, and cardiac index were measured before and after positional change. Results: The total incidence of hypotension after the BCP was 93.65%, but was not significantly different among the 3 groups. However, there was a significant difference in trends between the groups for MAP for 5 minutes after BCP ( P = .028). Comparison of changes in MAP at 1 minute compared to post-induction MAP was significantly different between group HP and group NS ( P = .014). Conclusion: Infusion of 0.5 and 1.0 μg/kg/min of phenylephrine for 5 minutes before the BCP has no preventive effect for incidence of hypotension. However, this study showed that 1.0 μg/kg/min of phenylephrine infusion for 5 minutes can attenuate the severity of hypotension.